Effects of nine months practice of martial arts on aerobic fitness in children and adolescentes - Saraiva, B. T.C. [UNESP]; Ritti-Dias, R. M.; Scarabottolo, C. C. [UNESP]; da Silva, A. L.F. [UNESP]; Tebar, W. R. [UNESP]; Christofaro, D. G.D. [UNESP] (Elsevier, 2023)
Objective: The aim of this study is to analyze the effects of nine months of martial arts practice (Judo and Muay Thai) on the aerobic fitness of children and adolescents. Methods: The sample consisted of 64 young people (41 boys and 23 girls) participating in a social project, aged between 6 and 15 years (9.06 ± 2.11). The children and adolescents were divided into three groups: Control (n = 26), Judo (n = 21), and Muay Thai (n = 17). Anthropometric measurements were performed, and the body mass index and somatic maturation were calculated. Maximum oxygen uptake (one-mile run/walk test) and agility (Shuttle Run) were measured. The intervention was performed for nine months, twice a week, for 60 minutes. Both groups (Judo and Muay Thai) performed 20 minutes of general exercises, 20 minutes of specific exercises for each modality, and 20 minutes of fight simulation and/or play activities. Results: At baseline the groups were similar for all characteristics and aerobic fitness. After 9 months, the MT (Δ= 1.71 ± 0.74) and Judo (Δ= 1.25 ± 0.68) groups presented increased oxygen consumption compared to the Control group (Δ= –1.85 ± 0.61), which presented decreased values (p-value = 0.001). Agility, however, did not present a difference between the groups (Control Δ= –0.52 ± 0.24, Judo Δ= –0.74 ± 0.27 and MT –1.08 ± 0.29). Conclusion: Nine months of martial arts training increased maximal oxygen consumption.
Effets de neuf mois de pratique des arts martiaux sur la condition aérobie chez les enfants et les adolescentes
Keywords: Adolescent; Aerobic Fitness; Child, Health; Martial Arts